Specific study of Imam Dawani’s philosophy of ethics - Naz, Farah; Al-Azhari, Ali Akbar (Al-Irfan, 2021)
As moral values lose their significance in society, it is necessary for scholars of religion to keep reviving the codes of life that embody virtues of humanity. In the history of Muslim moral thought, there is an abundance of literature on moral values as honesty, kindness, generosity, loyalty, decency, patience, gratitude, compassion and many more. Among the scholars who have enriched Muslim moral thought through their deep wisdom, Allama Jalal ud Din Dawani ranks as prominent. His prolific services to the fields of religion and morality addressed the moral dilemmas of 15th century through extracting inspiration from Aristotle and Naseer ud din Tusi. Being a learned scholar of Islam, he produced a philosophy of ethics (Akhlaq e Jalai) that contained his interpretations of religion, sufism and morality. Through categorizing individuals into different ranks based on ethics, he provided a default ladder for self-awareness and self-improvement. During his course of producing literature, Allama Jala ud Din Dawani did not confine his study to the analysis of a lay man’s morality alone. Rather, in his teachings, he also gave politics its due share. According to Dawani, a just ruler, guided by religion and intellect, is requisite for maintaining an ethically sound society. So, Dawani had a complete blueprint for transforming society into a robust edifice of goodness. It is noteworthy that his ideas did not expire with time. They lingered on, entering different eras and enlightening different scholars. This fact signifies the flexibility of his teachings that is receptive to evolving times. Even in the present age, there is lavish food for thought in his writings for the incumbent generations.